Validation and readability analysis of a psychoeducational manual to promote adherence behaviors in adults with asthma - Isaías Vicente Lugo-González; Yuma Yoaly Pérez Bautista (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2023)
Educational programs are ideal approaches to impro-ve treatment adherence and asthma control, for exa-mple,patienteducationmaterials,whichshouldideally be evidence-based and built to improve health education. The purpose of this work was vali-date by experts and analyze the level of readability of a psychoeducational manual to promote adheren-ce behaviors and disease control in adults with asth-ma. The manual was evaluated by 9 expert judges in asthma and health psychology, content validity was analyzed with the Osterlind index and reading diffi-culty with the INFLESZ index. The manual obtained an excellent evaluation of its content with an Oster-lind index of 0.98 and in the reading difficulty analysis it obtained a score of 67.74, evidence of a material that is very easy to read. The findings show the importance of building educational materials evidence-based and statistical indicators. Asthma patients are guaranteed to have access to quality, easy-to-understand material.